Buyer Power and Product Innovation: Empirical Evidence from the German Food Sector. - Christoph R. Weiss; Antje Wittkopp (Kiel University, Department of Food Economics and Consumption Studies, 2003)
Substantial increases in retail concentration (particularly in Europe) raise concerns about the welfare implications for consumers. In a formal model, we argue that retailer market power reduces upstream firms incentives to introduce new products. On the basis of a survey of firms in German food manufacturing, the results of a negative binomial regression model supports the proposition of a detrimental effect of retailer market power on product innovations. This effect is mitigated if manufacturing firms also have some market power (countervailing power). Innovations are positively related to firm?s market share in food manufacturing.
Keywords: L1; O31; L66; 330; Retailer market power; product innovation; food manufacturing; Lebensmitteleinzelhandel; Nachfragemacht; Innovation; Nahrungsmittelgewerbe; Wirtschaftskonzentration; Schätzung; Deutschland